Scorer le geste chirurgical de 1 à 5 - Nicolas El Haïk-Wagner (Revue d'anthropologie des connaissances)
Against a backdrop of hyperspecialisation, high claims rates and the delegitimisation of companionship, the university surgical community is seeking to assess the performance of practitioners and develop alternatives to companionship. This article describes the research of a reformer seeking to import a new technique for learning how to perform a procedure, deliberate practice, from top-level sport. His experiments involve carrying out procedures under simulated conditions, filmed and then evaluated in a standardised way. Despite its modesty, this system is raising high expectations. These small numbers help a multi-positioned university surgeon to enrol a series of institutional and insurance players to reform surgical learning and science and promote partial standardisation of techniques.